Non-homologous DNA increases gene disruption efficiency by altering DNA repair outcomes - C. D. Richardson (Nature Portfolio, 2016)
CRISPR-Cas9 mediated gene editing has begun to revolutionize molecular biology, but editing efficiencies can vary greatly between reagents. The authors show that the addition of single-stranded non-homologous DNA stimulates gene disruption by favouring error-prone DNA repair.